Pelanggaran Lalu Lintas Dengan Menggunakan Kendaraan Atas Nama Orang Lain Dalam Perspektif Nilai Keadilan - Apriansya Sinatra; Wandi Saputra; Muhammad Hendri Yanova; M. Febry Saputra (Scholar Center, 2022)
The goal to be achieved in this legal research is to find out about the position of ownership in imposing sanctions on vehicle owners for traffic violations through Electronic Traffic Law Enforcement by other people which reflects the value of justice. In this study, normative research is used, namely research that obtains legal materials by collecting and analyzing legal materials related to traffic violations by using vehicles on behalf of other people in perspective of the value of justice. The nature of the research in writing this thesis is the nature of prescriptive research, namely the nature of research that re-examines according to legal theory against norms that are considered to be vague (vage of norm) and finds ideal and most applicable answers. The results of this study indicate that: First, enforcement of traffic violations through Electronic Traffic Law Enforcement uses the CCTV feature to identify evidence of traffic violations. The data taken in the form of license plate numbers, types of vehicles, and types of violations identified. Second, the Electronic Traffic Law Enforcement system is still not equipped with a facial scan feature to determine whether the perpetrator of the violation is really the owner of the vehicle. In addition to vehicles detected by Electronic Traffic Law Enforcement, owners who do not commit violations must take legal action to prove their guilt.